2020
DOI: 10.1016/j.cretres.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Shajia, a new genus of polyconitid rudist from the Langshan Formation of the Lhasa block, Tibet, and its palaeogeographical implications

Abstract: The Open University's repository of research publications and other research outputs Shajia, a new genus of polyconitid rudist from the Langshan Formation of the Lhasa Block, Tibet, and its palaeogeographical implications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…The marine environment in western Qiangtang started during the Late Triassic‐Early Jurassic and was ceased by the Late Jurassic, with marine rocks unconformably overlain by Upper Cretaceous continental red beds (A. Ma et al., 2017). In contrast, the marine environments in western Lhasa continued to develop until Mid‐Cretaceous (Rao et al., 2020). The arrival of Qiangtang detritus into western Lhasa basins at ∼111–116 Ma marks a minimum age for the initial Lhasa‐Qiangtang collision (S. Li et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The marine environment in western Qiangtang started during the Late Triassic‐Early Jurassic and was ceased by the Late Jurassic, with marine rocks unconformably overlain by Upper Cretaceous continental red beds (A. Ma et al., 2017). In contrast, the marine environments in western Lhasa continued to develop until Mid‐Cretaceous (Rao et al., 2020). The arrival of Qiangtang detritus into western Lhasa basins at ∼111–116 Ma marks a minimum age for the initial Lhasa‐Qiangtang collision (S. Li et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Rudist faunas from the Himalaya-Karakorum-Tibet range and the Tarim basin are known from the late Aptian and are well-developed into the Maastrichtian (LAN & WEI, 1995;WEN et al, 1998;SCOTT et al, 2010;RAO et al, 2015RAO et al, , 2017RAO et al, , 2020SHA & CESTARI, 2016;RAO, 2019). SCOTT et al (2010) reported 36 genera and 44 species occurring in the region in the Albian-Maastrichtian interval.…”
Section: Comparison Of the Aksai Chin Fauna With Other Neotethys Faunasmentioning
confidence: 99%